SELF EFFICACY, PENYESUAIAN DIRI PADA MAHASISWA NUSA TENGGARA TIMUR DI SURABAYA - Endah Sulistyoningrum; Starry Kireida Kusnadi (Fakultas Psikologi Universitas Wijaya Putra, 2020)
This research aims to find out the relationship of Self efficacy with self-adjustment in new students who feel able to overcome challenges in college will engage more deeply in the learning process as well as various experiences that exist in college, so that students with high self efficacy will face tasks, problems, and activities vigorously and not easily give up, can motivate themselves cognitively to act more consistently and directedly. This research was conducted on new students from NTT in UWP Surabaya semesters 1 and 2 with the number of research subjects 50 students, consisting of 18 male and 32 female students. Data collection technique using simple random sampling Data collection tool in the form of self efficacy questionnaire consisting of 27 items, while self adjustment questionnaire consisting of 53 items. The data analysis was conducted with pearson product moment correlation test statistical technique with the help of Windows Series 20 SPSS (Statistical Package for Social Science) program. From the analysis of research data obtained correlation value between self efficacy with self adjustment of 0.279 with p of 0.827. This suggests that there is a significant correlation between self efficacy and self-adjustment. This means that the higher the self efficacy, the higher the self-adjustment of new students from NTT at UWP Surabaya and vice versa the lower the self efficacy, the lower the adjustment of new students from NTT in UWP Surabaya